Regional disparities in the income distribution - Мороз, Катерина Вікторівна (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
This paper investigates features of the socio - economic development in the context of unequal income distribution. On the basis of a comparative analysis of a set regional development indicators (real disposable income, the Human development index, the Gini coefficient), region of Ukraine were united in clusters, which allowed to characterize certain territories in terms of opportunities for the realization of human potential.